AB0303 Tocilizumab in rheumatoid arthritis – annual interim analysis of the german non-interventional study ichiban. (23rd January 2014) - Specker, C.; Kaufmann, J.; Kellner, H.; Bohl-Bühler, M.; Schwenke, H.; Vollmer, M. A.; Kapelle, A.; Zinke, S.; Hofmann, M. W.; Hellmann, P.; Fliedner, G.
Abstract : Background: The ICHIBAN study collects routine clinical data to evaluate the effectiveness and safety of tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) in real world practice over a period of 2 years. Methods: The start of this prospective, non-interventional study was in February 2010. The target recruitment is 4000 patients. Clinical data of RA patients, their therapies, therapeutic responses, patient reported outcomes and adverse events are collected in the process of normal practice using an online database with structured web forms. Results: As of 1 st December 2012, baseline data for 1895 patients were available. In 490 of these patients the observation period was at least 76 weeks under TCZ treatment, or treatment was interrupted or changed (analysis was performed according to LOCF method). The total TCZ exposure was 2299.8 patient years. 74.9% of the 1895 patients were female, the mean age was 56.3 years. Mean duration of RA was 10.0 years and baseline DAS28 was 5.1. 72.0% of the patients had concomitant diseases. 69.8% were pre-treated with TNF-alpha inhibitors, 28.0% exclusively with synthetic DMARDs. At baseline 40.1% of TCZ-treated patients did not receive any additional DMARD, while 46.0% were treated in combination with MTX. At W76, 34.0% of the patients (n=149/438) achieved DAS28 remission (<2.6). A moderate or good EULAR response was seen in 29.1% or 56.9% of the patients, respectively. The mean tender joint count (TJC) decreased from 9.6 to 3.5, the mean swollen joint count from 6.9 to 2.1. Mean ESR decreased from 35.5 to 10.6 mm/1h and CRP from 3.5 to 0.6 mg/dl. Data on patient reported outcomes (PRO) at week 76 are shown in Tab. 1. In 12.0% of the initially TCZ-treated patients (n=59/490) treatment was changed during the observational period. 1916 adverse events were reported (in 751/1895 patients; 83.3/100 patient years). 404 of these events were infections (17.6/100 patient years). 370 serious adverse events were reported (in 222 patients; 16.1/100 patient years), 219 of which (59.2%) were judged at least "unlikely" in relation to TCZ. Conclusions: In daily practice TCZ treatment of patients with moderate to severe RA demonstrates good efficacy also in monotherapy and confirms the known safety profile. The first 490 patients having completed the observational period of at least one and a half years show clear improvements in all recorded RA parameters, as well as further improvements compared to the results after the first year of treatment. Disclosure of Interest: C. Specker Grant/research support from: Has received honoraria from Chugai for advising in study design and conduction and fees for talks, in summary less than €10.000/year, J. Kaufmann: None Declared, H. Kellner: None Declared, M. Bohl-Bühler: None Declared, H. Schwenke: None Declared, M. Vollmer: None Declared, A. Kapelle: None Declared, S. Zinke: None Declared, M. Hofmann: None Declared, P. Hellmann: None Declared, G. Fliedner Grant/research support from: Has received honoraria from Chugai for advising in study design and conduction and fees for talks, in summary less than €10.000/year